2011
DOI: 10.1051/0004-6361/201016088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a low electron distribution cutoff on multiwavelength spectra and light curves of GRB afterglows

Abstract: Aims. We investigate the behavior of the frequency-centered light curves expected within the standard model of gamma ray bursts, allowing the maximum electron energy (γ max ) to be a free parameter that may take low values. Methods. We solve the spatially averaged kinetic equations that describe the simultaneous evolution of particles and photons, obtaining the multi-wavelength spectra as a function of time. From these we construct the frequency-centered light curves with an emphasis on the X-ray and optical b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Additionally, we have demonstrated that a flattening or rebrightening segment in the forward shock light curve is expected in the case of purely Maxwellian electron injection in a waveband where the observed flux gradually becomes dominated by the inverse Compton component, as described by Petropoulou et al (2011). Such flattenings are observed in a large fraction of X-ray light curves, but their physical origin is still under debate.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, we have demonstrated that a flattening or rebrightening segment in the forward shock light curve is expected in the case of purely Maxwellian electron injection in a waveband where the observed flux gradually becomes dominated by the inverse Compton component, as described by Petropoulou et al (2011). Such flattenings are observed in a large fraction of X-ray light curves, but their physical origin is still under debate.…”
Section: Discussionmentioning
confidence: 89%
“…It is notable that a flattening or a slight rebrightening appears in all the cases with a Maxwellian electron injection. The flat segment is produced when the synchrotron component moves out of the observed energy range and is gradually replaced by the inverse Compton emission, similarly as described by Petropoulou et al (2011), who simulated the external shock emission from powerlaw electrons with a narrow energy distribution. A similar effect is also seen in the simulations of Stern & Poutanen (2004).…”
Section: Emission From a Maxwellian Distribution Of Injected Electronsmentioning
confidence: 99%
“…Possible models include late-time energy injection [111,113,114], long-lasting central engine activity [115,116], time dependence of shock microphysics [117,118], viewing angle effects [119,120], shock coasting in a wind medium [121], or contribution from SSC emission [122]. These predict different high-energy emission signatures (e.g.…”
Section: Physics Of Grbsmentioning
confidence: 99%
“…This injection can take on all sorts of forms, including long-term source luminosity, 189,190 conversion of Poynting flux from the ejecta [165][166][167] or late time shells catching up. 201,[221][222][223] Alternative explanations not including jet dynamics are changing microphysics of the emission 219,224,225 or viewing angle effects. 226 An attractive candidate to provide long-term injection of energy is a magnetar, which would add energy into the system when shedding its rotational energy following its formation in the event that triggers the GRB.…”
Section: Persistent Injection Of Energymentioning
confidence: 99%